The Relationship of the Baltic and Tocharlan Denominatives (Inanimate Nature) - Chomičenkienė, Aleta (Acta Orientalia Vilnensia, 2000)
The article analyses about 30 lexemes that denote phenomena of inanimate nature, i.e. elements of the physical world. The comparisons presented in the article are not exactly traditional, as lexemes compared can be a Lith. verb and a Toch. noun or adjective. Most of the pairs compared are interesting from the semantic, but not the structural, point of view, as structurally they do not have much in common in the Baltic and Tocharian languages.Pairs of cognates in the Baltic and Tocharian languages were first of all grouped in accordance with the elements (Wood, Fire, Water, Earth, Metal). There are no cognates in the Baltic and Tocharian languages to denote the parts of the world (i.e. East, West, etc.) There are no obvious cognates of a similar structure to denote seasons, as the parallel of the Toch. A *wäs–ri ‘a meadow’ and Baltic *u̯asenā ‘spring – summer’ remains hypothetical. As for the names of the parts of the day, we have only the name of the night witnessed: Lith. naktis ‘night’ and Toch. nekcīe ‘at night’.3 lexemes that belong to the Fire element (flame, heat, warmth) are of a very similar structure and semantics. They are stem reflexes of heteroclitic declension: Old Pruss. panno ‘fire’ and Toch. A por, B puwar ‘fire’, as well as two lexemes that denote “warmth” and function as derivatives of the Indo–European verb stems with the suffix –m–: these are the Lith. svelme ‘heat’ and Toch. A slam, B sleme ‘flame’; Old Pruss. gorme ‘heat’ and Toch. çärme ‘warmth’.As for the cognates that belong to the Wood element, 4 pairs were found: one of them is non–derivative and can not be structurally decomposed, i.e. East Balt. *de/ar–u̯–ā/*dre–u̯–ē ‘resin; a hole in a tree’ and Toch. AB or ‘wood’, which lost the initial root consonant d–. Another pair of words is derivatives of the IE verb *sthā ‘to stand up, to stand’ with a very old suffix *–mōn, cf. East Balt. *stāmōn ‘the stem of a tree’ and Toch. A tām, B stām ‘a tree’ (in the Baltic languages this lexeme is characterised by the branching of the meaning).The two remaining pairs of cognates both in the Baltic and Tocharian languages are derivatives of the IE verb *seku– ‘to go, to flow’ and *steup– ‘to beat, to hit’, cf. Balt. *sakai ‘resin’, Toch. A saku, sekwe ‘puss’, also Lat. stups ’a stump’ and Toch. A top, stow ‘a stick’ (these deverbatives both in the Baltic and Tocharian languages belong to the o–stem).No cognates denoting specific trees were found in both groups of the languages under discussion.In the group of the cognates that belong to the Earth element, the one which denotes the earth itself is of a doubtful character, as, starting with the Baltic languages taken separately, the problem of etymological interpretation of the lexeme *źemē– / ‘the earth’ arises. Etymological literature usually adds the Toch. A tka, B ke ‘the earth’ to this etymological group, though the phonetic structure of the beginning of the root is very different.In the Tocharian language, the IE *ped–/*pēd–/*pod–/*pōd– ‘foot, sole’ are widely applied for naming land and soil (the sole is the part of the foot which has an immediate contact with the ground) nil reflexes of ‘land, soil’: Toch. A petwe ‘closed land, edge, bank’ and Toch A päts, B ptsa (Acc.Sg.) ‘soil, land’ < IE ped– reflexes. One of the meanings of the Lith. padas ‘the bottom part of the oven’ is isolated and not so widely used in the present–day Lithuanian.For naming hollow places, flexion derivatives of the IE verb *dheub–/*dhub– ‘to become / make hollow’ are witnessed both in the Baltic and Tocharian languages: Lith dauba ‘ravine’, Old Prus. dambo ‘ravine, valley’ and Toch. A top, B taupe “mine” (only in the Baltic languages they are ā–stem, and in the Tocharian o–stem nouns.)The two remaining pairs of words must be independent Baltic and Tocharian derivatives of the IE verb roots, although the words for tiny particles ‘the dust of rain’ in both groups are of a similar structure and semantics, cf. Lith duja ‘a speck of dust’ and Toch. A twe, B tweye ‘dust, steam’. The words for clay, dirt, wet soil are coined with the help of the suffix –no– [cf. Lith liūnas ‘quag’ and –mo– (Toch. A lyom ‘clay, dirt’)].In the Metal group, only one pair of cognates denoting gold was found; and these are deverbatives of the IE *au(e)s– ‘to shine’. In the Baltic and Tocharian languages they differ in the degree of vowel gradation, cf Lith auksas, Old Pruss. ausis and Toch. A wäs, B yasā,ysā (a reduced degree of the vowel gradation).Quite a number of cognates (8 pairs) were found in both groups of languages for the Water group (denoting rain, the process of raining, inclement weather). The words of a similar structure are West Balt. *apis/*apē and Toch. AB āp “river” < Balt. *(i̯)aur–/ *(i̯)ūr– ‘wet place, sea’ and Toch. A wār, B war ‘water’(a reduced degree of the vowel gradation).Of a different derivative pattern are the Old Pruss. suge ‘the process of raining’ and Toch. A swase, B swese ‘raim’ < IE verb *seu–/*sū– “to rain”, as weil as Toch A tärkär, B tarkär ‘cloud’ (cf. a related East Lith. verb *derg–/*derk– ‘(for the weather) to be inclement’ and another, of a more distant relationship, Lith. dargana “inclement weather”).The derivatives of the Lith. verb roots *lei̯–ti ‘to pour water’ and *pers– ‘make damper’ (or independent verbs) are witnessed either in one or the other group of the languages under question), cf. Lith. lieti ‘to pour’ and Toch. A adj. lyi ‘damp’, Toch. A pärs ‘to make damp’ and Lith. purkšti ‘sprinkle’, purslas ‘a tiny drop’, etc.Cognates of a different degree of relationship in the Baltic and Tocharian languages witness that the concepts of dampness, rain, wet soil are very popular in the languages compared and are an indirect proof of the same climatic zone where the ancestors of the Baltic and Tocharian people resided.